2001
DOI: 10.1093/humrep/16.6.1237
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation of female mice delays embryonic and fetal development

Abstract: Mouse and human embryos, cultured in vitro, undergo a delay in development compared with those grown in vivo. This delay can be caused by suboptimal culture conditions, but possible influences of ovarian stimulation cannot be excluded. The objective of this study was to test the hypothesis that both in vitro and in vivo, preimplantation embryonic development and postimplantation fetal development are impaired in superovulated female mice when compared with naturally cycling controls. A delay in in-vitro blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 29 publications
2
128
1
2
Order By: Relevance
“…In the laboratory mouse, for example, it produces a delay in preimplantation development of 2 to 7 h per cycle [18,39]. Depending on the strain of mice analyzed, during in vivo In light of these data, it has been calculated that embryos maintained in vitro throughout preimplantation development may be delayed by an entire day at the blastocyst stage [12,37,49]. The processes of compaction, blastulation and blastocyst expansion are thus completed in vitro with progressively increasing temporal delays, likely leading to a loss of developmental competence and a reduction in the chance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory mouse, for example, it produces a delay in preimplantation development of 2 to 7 h per cycle [18,39]. Depending on the strain of mice analyzed, during in vivo In light of these data, it has been calculated that embryos maintained in vitro throughout preimplantation development may be delayed by an entire day at the blastocyst stage [12,37,49]. The processes of compaction, blastulation and blastocyst expansion are thus completed in vitro with progressively increasing temporal delays, likely leading to a loss of developmental competence and a reduction in the chance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that superovulation of female mice delayed embryonic and fetal development [3,34]. The possible explanation is that superovulation increases the proportion of chromosomal abnormalities in oocytes in rats and uterine horn is incapable of nourishing large number of blastocysts tyring to implant and also to develop in to a fetus [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been common practice to treat infertility in humans. The use of high dose of exogenous hormones has recently caused much debate surrounding their effects on oocyte maturation [3,4]. Because imprint acquisition has been shown to occur relatively late in oogenesis, the establishment of these imprints may be susceptible to exogenous hormone treatments [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…First, both rhFSH and PMSG therapies adversely effect the uterine environment in mice resulting in a reduced pregnancy rate compared to randomly cycling adult females (17)(18)(19). Second, despite a significant increase in the number of developing embryos present following ovarian hyperstimulation, the litter size is physiologically restrained by the physical limitations of the mouse uterus (20).…”
Section: Discussionmentioning
confidence: 99%